Activation of photoprotective winter photoinhibition in plants from different environments: a literature compilation and meta‐analysis. Issue 4 (24th February 2015) - Míguez, Fátima; Fernández‐Marín, Beatriz; Becerril, José María; García‐Plazaola, José Ignacio
Abstract : Overwintering plants face a pronounced imbalance between light capture and use of that excitation for photosynthesis. In response, plants upregulate thermal dissipation, with concomitant reductions in photochemical efficiency, in a process characterized by a slow recovery upon warming. These sustained depressions of photochemical efficiency are termed winter photoinhibition (WPI) here. WPI has been extensively studied in conifers and in few overwintering crops, but other plant species have received less attention. Furthermore, the literature shows some controversies about the association of WPI with xanthophylls and the environmental conditions that control xanthophylls conversion. To overview current knowledge and identify knowledge gaps on WPI mechanisms, we performed a comprehensive meta‐analysis of literature published over the period 1991–2011. All publications containing measurements of Fv/Fm for a cold period and a corresponding warm control were included in our final database of 190 studies on 162 species. WPI was estimated as the relative decrease in Fv/Fm. High WPI was always accompanied by a high (A + Z)/(V + A + Z). Activation of lasting WPI was directly related to air temperature, with a threshold of around 0°C. Tropical plants presented earlier (at a temperature of >0°C) and higher WPI than non‐tropical plants. We conclude that (1) activation of a xanthophyll‐dependent mechanism of WPI is a requisite for maintaining photosynthetic structures at sub‐zero temperatures, while (2) absence (or low levels) of WPI is not necessarily related to low (A + Z)/(V + A + Z); and (3) the air temperature that triggers lasting WPI, and the maximum level of WPI, do not depend on plant growth habit or bioclimatic origin of species.